2020
DOI: 10.3390/s20195576
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of P300-Based Brain–Computer Interfaces for Home Appliances Control by Data Balancing Techniques

Abstract: The oddball paradigm used in P300-based brain–computer interfaces (BCIs) intrinsically poses the issue of data imbalance between target stimuli and nontarget stimuli. Data imbalance can cause overfitting problems and, consequently, poor classification performance. The purpose of this study is to improve BCI performance by solving this data imbalance problem with sampling techniques. The sampling techniques were applied to BCI data in 15 subjects controlling a door lock, 15 subjects an electric light, and 14 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As the total number of participants to whom a rhythm-control strategy was applied was relatively low (imbalanced data), we first compared four methods of resampling: synthetic minority oversampling technique (SMOTE) [ 40 , 41 ], random oversampling, random undersampling, and Tomek links undersampling [ 42 ], as well as the use of raw features. Resampling was performed only in the training set.…”
Section: Methodsmentioning
confidence: 99%
“…As the total number of participants to whom a rhythm-control strategy was applied was relatively low (imbalanced data), we first compared four methods of resampling: synthetic minority oversampling technique (SMOTE) [ 40 , 41 ], random oversampling, random undersampling, and Tomek links undersampling [ 42 ], as well as the use of raw features. Resampling was performed only in the training set.…”
Section: Methodsmentioning
confidence: 99%
“…These data were imbalanced, possibly posing a problem for classification. Our previous study ( Lee et al, 2020 ) showed that adjusting the penalty parameter C could resolve the problem of imbalance slightly, but the resulting improvement in accuracy was only marginal. According to this study, we did not adjust C in the online BCI experiment.…”
Section: Methodsmentioning
confidence: 99%
“…As a noninvasive neuroimaging modality, EEG is one of the oldest techniques used to measure neural activation in the human brain for diagnosis or brain–computer interface (BCI) purposes ( Naseer and Hong, 2013 ; Khan and Hong, 2017 ; Tanveer et al, 2019 ). Since they are portable and have the advantage of higher temporal resolution, EEG-based BCI applications have been widely designed for daily use (e.g., home automation control devices, EEG-based wheelchairs, brain disorder detection platforms) ( Kim et al, 2019 ; Lee T. et al, 2020 ; Rashid et al, 2020 ; Yang et al, 2020b ). EEG measurements are based on electrical potential differences between different electrodes on the scalp.…”
Section: Introductionmentioning
confidence: 99%